2017
DOI: 10.1002/jcu.22443
|View full text |Cite
|
Sign up to set email alerts
|

Perception of point‐of‐care ultrasound performed by emergency medicine physicians

Abstract: Study respondents demonstrated limited confidence and utilization of EM-POCUS in this institution. Increased understanding of EM-POCUS training and expanded image availability may improve consultant utilization. Future studies, performed nationally, should further describe the value of EM-POCUS to consultant services. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45:408-415, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 10 publications
6
40
0
Order By: Relevance
“…POCUS utility could also be advocated among emergency physicians as an extended bedside examination or procedure-guiding tool, 9 supported by credentialing and training programmes that involve bedside supervision and teaching, especially for junior medical staff and trainees. The utility could potentially be promoted by an increased number of POCUS machines in the hospital; an internal credentialing programme targeting potential operators (i.e.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…POCUS utility could also be advocated among emergency physicians as an extended bedside examination or procedure-guiding tool, 9 supported by credentialing and training programmes that involve bedside supervision and teaching, especially for junior medical staff and trainees. The utility could potentially be promoted by an increased number of POCUS machines in the hospital; an internal credentialing programme targeting potential operators (i.e.…”
Section: Limitationsmentioning
confidence: 99%
“…registrars and CMOs); and the development of internal, state-wide or national-specific guidelines. POCUS utility could also be advocated among emergency physicians as an extended bedside examination or procedure-guiding tool, 9 supported by credentialing and training programmes that involve bedside supervision and teaching, especially for junior medical staff and trainees. 8,[10][11][12] Further researches and studies can be other identified solutions.…”
Section: Suggestion To Improve Pocus Utility Ratementioning
confidence: 99%
“…Many studies have shown that clinicians are uncomfortable with their level of skill using PoCUS and would be interested in improving their skills . Moreover, confidence in the use of ultrasound appears to wane over time, possibly from lack of use or ongoing training .…”
Section: Pocus Training In Australia and Worldwidementioning
confidence: 99%
“…Pressure put on EPs to move patients quickly to keep good throughput for a particular institution could be discouraging physicians from doing EM-POCUS and we did not ask that question. However, from an economic perspective, the physician time involved to obtain a bedside ultrasound may be wasted time if the practitioner does not trust the images obtained and continues to order confirmatory "gold standard" tests instead of relying on the ultrasound and his/her clinical judgment.Hansen et al12 reported the results of a survey evaluating how EM-POCUS images and results were incorporated into the clinical decision making of non-EM residents who were asked to consult on a patient. Sixty-one residents representing general surgery, internal medicine and obstetrics and gynecology responded to nine questions regarding their utilization of and confidence in EM-POCUS findings as…”
mentioning
confidence: 99%
“…EP concerns regarding the use of EM-POCUS The overall usage of reported EM-POCUS findings by consultants was 68.9%; however, only 47.5% reported being comfortable with using EM-POCUS reports 12. …”
mentioning
confidence: 99%